Gunshot wound to the abdomen: multivisceral lesions and liver pedicle - Bergalli, Luis E; Castiglioni, Juan C (Cirugía del Uruguay, 1972)
This is a case. of a bullet wound in the abdomen, with multivisceral lesions including the hepatic pedicle, kidney, duodenum and liver, its treatment and evolution.